Regioselective Asymmetric Allylic Alkylation Reaction of α‐Cyanoacetates Catalyzed by a Heterobimetallic Platina‐/Palladacycle. Issue 1 (16th December 2015) - Weiss, Marcel; Holz, Julia; Peters, René
Abstract: Allylic substitution reactions provide a valuable tool for the functionalization of CH acidic pronucleophiles. Often, control over the stereocenter generated at the nucleophilic reactant is still a challenge. The majority of studies that address this issue employ metal complexes with a low metal oxidation state (e.g. Pd 0 ) to form allyl complexes through oxidative addition. In this article we describe the use of heterobimetallic Pt II /Pd II complexes, which probably activate the olefinic substrates through an SN 2′ pathway. The reaction of α‐cyanoacetates delivers linear allylation products with exclusive regioselectivity and high E / Z ‐selectivity for the new C=C double bond. Although the enantioselectivities attained are moderate, they are significantly higher than with related mono‐Pd II or ‐Pt II catalysts or the corresponding bis‐Pd II complex, which indicates cooperation of the different metals. Control experiments suggest simultaneous activation of both reaction partners. Abstract : A Pt II /Pd II heterobimetallic catalyst has been used for stereo‐ and regioselective allylation reactions of α‐cyanoacetate pronucleophiles with allylic acetates. In the planar chiral ferrocene‐based mixed pallada‐/platinacycle both metals likely cooperate by simultaneous activation of both substrates. Enantioselectivities are higher than for the corresponding bis‐palladacycle catalyst, which shows the impact of the Pt center.